The Analytical Lexicon to the Greek New Testament - Mounce, William D (Grand Rapids, MI : Zondervan Pub. House, 1993)
Study aid to Greek New Testament. Based on the latest Greek text (USB 3rd ed., rev.). Includes both accepted and variant readings, up-to-date definitions etc
Nouns and adjectives : The basic rules governing case endings ; Case endings ; Article ; Nouns ; Adjectives -- Verb formation ; Augment ; Reduplication ; Verbal tense formation ; Tense and mood formatives ; Thematic and athematic conjugations ; Personal endings -- Tense formation : Master indicative verb chart ; Overview of the thematic conjugation ; Present indicative ; Imperect indicative ; Imperfect indicative ; Future indicative ; Aorist indicative ; Perfect active indicative/pluperfect ; Perfect middle/ passive indicative ; Aorist/ future passive ; Subjunctive ; Optative ; Imperative ; Infinitive ; Participle -- Analytical lexicon
English and Greek
Includes index
English and Greek
Keywords: Bible. -- Dictionaries; Greek language, Biblical -- Dictionaries -- English; Greek language, Biblical - Dictionaries - English; Bible. N.T. - Language, Style; Reference works